Recurrent Respiratory Tract Infection in a 24-Year-Old Female Secondary to a Foreign Body Aspiration. (10th March 2021) - Sukahri, Samshol; Mohd Zim, Mohd Arif; Hadi, Mohd Firdaus; Mohd Firdaus, Mohd Al-Baqlish
Abstract : Foreign body aspiration (FBA) is a common problem necessitating prompt recognition and early treatment to minimize the potentially severe and sometimes fatal consequences. We presented a 24-year-old girl who was admitted for chronic cough and recurrent pneumonia associated with constitutional symptoms. She was feverish with a temperature of 39°C and had tachycardia and tachypnoea with an oxygen saturation of 98%. Investigations revealed leukocytosis. CXR showed right lower lobe consolidation, and CT thorax demonstrated collapse consolidation of the right middle and lower lobe, along with associated dilated segmental bronchioles and diffuse patch ground-glass opacity in both lung fields. Bronchoscopy revealed a pen cap at the entrance of the right lower lobe. Patient symptoms improved after removal of the foreign body. In patients with recurrent chest infection, the physician should check for the possibility of FBA and prompt for a referral to a tertiary center for further evaluation.